Pedicled Cervical Lymphoadipose Tissue for Volume Reconstruction after Superficial Parotidectomy - Kyle P. Davis; Amy L. Fraser; Elizabeth O. Shay; Michael W. Sim (Case Reports in Otolaryngology)
Volume restoration is often required after parotidectomy due to the resultant facial contour deformity. Common procedures include local pedicled flaps, such as the sternocleidomastoid muscle flap, fat grafting, and even autologous free flaps, for more extensive defects. Local pedicled flaps have the advantage of a single surgical site, which spares the patient the added morbidity of a separate fat graft donor site, while simultaneously reducing the operative time. We report two cases of a novel reconstructive option using pedicled level I and II cervical lymphoadipose tissue for volume restoration after superficial parotidectomy. This reconstruction would be useful for patients with benign parotid lesions and inferior parotid defects. In addition, with maintained blood supply to this tissue, it would likely provide sustained bulk over time.